IMPLEMENTATION OF DEFAULT SETTLEMENT THROUGH A SIMPLE LAWSUIT (Case Study Decision Number: 8/PDT.G.S/2020/PN.Yyk.) - Chumbhadrika, Chitto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
In the principle of civil procedural law in Indonesia, one of which is the principle of simple, fast and low cost. The process of settling a simple lawsuit or commonly referred to as a small claim court is a procedure for examining a civil lawsuit with a maximum value of Rp. 500,000,000 million which was solved with simple procedures and proofs. Problem formulation: 1). How is the simple lawsuit mechanism according to the Supreme Court Regulation Number 2 of 2015 as amended by PERMA Number 4 of 2019 in the implementation of the simple lawsuit trial? And what is the judge's consideration in Decision Number 8/PDT.G.S/2020/PN.Yyk regarding a simple lawsuit? The application of the research method is in the form of normative juridical, meaning that the issues raised, discussed and described in this study are focused on applying the rules or norms in positive law. This study discusses the parties in the Small Claim Court consisting of plaintiffs and defendants, both individuals and legal entities, each of which cannot be more than one, unless they have the same legal interest. The place of residence as stated in Article 4 paragraph (3a) of Perma Number: 4 of 2019 which states that